Neutrophil recruitment by chemokines Cxcl1/KC and Cxcl2/MIP2: Role of Cxcr2 activation and glycosaminoglycan interactions. Issue 4 (2nd September 2020) - Sawant, Kirti V.; Sepuru, Krishna Mohan; Lowry, Emily; Penaranda, Brigith; Frevert, Charles W.; Garofalo, Roberto P.; Rajarathnam, Krishna
Abstract: Chemokines play a crucial role in combating microbial infection by recruiting blood neutrophils to infected tissue. In mice, the chemokines Cxcl1/KC and Cxcl2/MIP2 fulfill this role. Cxcl1 and Cxcl2 exist as monomers and dimers, and exert their function by activating the Cxcr2 receptor and binding glycosaminoglycans (GAGs). Here, we characterized Cxcr2 G protein and β‐arrestin activities, and GAG heparan sulfate (HS) interactions of Cxcl1 and Cxcl2 and of the trapped dimeric variants. To understand how Cxcr2 and GAG interactions impact in vivo function, we characterized their neutrophil recruitment activity to the peritoneum, Cxcr2 and CD11b levels on peritoneal and blood neutrophils, and transport profiles out of the peritoneum. Cxcl2 variants compared with Cxcl1 variants were more potent for Cxcr2 activity. Native Cxcl1 compared with native Cxcl2 and dimers compared with native proteins bound HS with higher affinity. Interestingly, recruitment activity between native Cxcl1 and Cxcl2, between dimers, and between the native protein and the dimer could be similar or very different depending on the dose or the time point. These data indicate that peritoneal neutrophil recruitment cannot be solely attributed to Cxcr2 or GAG interactions, and that the relationship between recruited neutrophils, Cxcr2 activation, GAG interactions, and chemokine levels is complex and highly context dependent. We propose that the ability of Cxcl1 and Cxcl2 to reversibly exist as monomers and dimers and differences in their Cxcr2 activity and GAG interactions coordinate neutrophil recruitment and activation, which play a critical role for successful resolution of inflammation. Graphical Abstract: Chemokine levels, chemokine monomer‐dimer equilibrium, CXCR2 activity, and GAG interactions, acting in concert determine neutrophil recruitment